Perkawinan Anak dalam Jebakan Sosio-Kultural Masyarakat Bajo Pesisir di Sulawesi Tenggara - Zainal, Asliah; Hasniran, Hasniran; Insawan, Husain; Zainal, Muhammad Asrianto (UIN Sunan Kudus, 2022)
Child marriage is a complex issue that is still rife in recent times, especially in marginalized communities. This study aims to analyze the social background and cultural construction that facilitates the context of child marriage in the Bajo community in Southeast Sulawesi. Primary data were collected through interviews with child brides, parents and local communities; make observations on the settlement, the behavior of the community and their interactions with each other, especially for child brides. Using a sociological perspective, this study finds that there are four factors that underlie the occurrence of child marriage cases, firstly the mindset and lifestyle that ignores risk; second, poverty in education, economy, and religion; third, live comfortably in a cultural shell; and fourth, a house without a private/intimate space. These four factors become the background context that traps the community as if they are unable to get out of the problem